Upaya Peningkatan Prestasi Non Akademik melalui Manajemen Sarana Prasarana di MA Al-Furqon Cimerak - Alfi Maulia Rahmah; Dian Herdiana; Riksa Iqomah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
This study aims to describe how efforts to increase non-academic achievement through the management of infrastructure at MA Al Furqon Cimerak. The research method used in this research is a case study method with a qualitative approach. The research subjects inthis study were school principals who were part of the curriculum manager, extracurricular coordinators, administrative staff and students. The results of the study show that efforts to increase non-academic achievement through management of infrastructure at MA Al Furqon Cimerak are carried out through renewal and provision of extracurricular infrastructure. Schools make various strategies such as providing the best trainers to hone students' talents, finding competent teachers, and actively facilitating students to participate in various competitions. In addition, the school principal also monitors teachers in providing good assistance and guidance to students so that they are enthusiastic and earnest in achieving